Foamed ceramics prepared by rare earth blast furnace slag and coal gangue and preparation method thereof

By ball milling and wet grinding of rare earth blast furnace slag, coal gangue, etc. with mixtures of low-melting point solid waste raw materials and talc powder, high value-added foamed ceramics are prepared, which solves the problem of difficulty in firing high-melting point materials and achieves efficient utilization and low-cost processes.

CN119349990BActive Publication Date: 2025-03-21BAOGANG GRP METALLURGICAL SLAG COMPREHENSIVE UTILIZATION & DEV CO LTD

Patent Information

Application Number
CN202411947788.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Due to the high melting point of rare earth blast furnace slag and coal gangue, it is difficult to directly prepare high-performance foamed ceramics, and the existing methods have problems such as low solid waste utilization, long sintering process time and high cost.

Method used

High added value foamed ceramics are prepared by ball milling and wet milling of rare earth blast furnace slag, coal gangue, crushed silica, low-melting point solid waste raw materials and talc powder. The method includes ball milling, wet grinding, drying, grinding and direct sintering, using low-melting point solid waste raw materials to reduce the firing temperature, and improving the physical properties of the ceramics through optimized proportions and process flow.

Benefits of technology

It realizes efficient utilization of rare earth blast furnace slag and coal gangue, reduces sintering temperature and time, improves the compressive strength and physical properties of foamed ceramics, and has low process cost and is environmentally friendly and green.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349990B_ABST
    Figure CN119349990B_ABST
Patent Text Reader

Abstract

The present application provides a foamed ceramic prepared by rare earth blast furnace slag and coal gangue and a preparation method thereof. The method of the present application includes ball milling raw materials including rare earth blast furnace slag, coal gangue, crushed silica, low melting point solid waste raw materials, and talcum powder until they pass through a 200-mesh sieve; adding water to the sieved raw materials and foaming agent for wet grinding to obtain a slurry; drying the slurry and grinding it to obtain a powder; spreading the powder in a mold and pressing it into a shape to obtain a molded blank; heating the molded blank to obtain a foamed ceramic. The preparation method of the present application adopts a direct sintering method to prepare foamed ceramics, which not only opens up a new way to mass-produce and high-value utilization of solid wastes such as rare earth blast furnace slag and coal gangue, but also solves the environmental pollution problem caused by solid wastes, and the prepared foamed ceramics have excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of resource utilization of solid waste, and in particular to a foamed ceramic prepared by rare earth blast furnace slag and coal gangue, and a preparation method thereof. Background Art

[0002] Foamed ceramics have the characteristics of high porosity, high strength, stable physical and chemical properties, etc. Due to its special structure of pores, foamed ceramic materials are widely used in the fields of construction, chemical industry, aerospace, biomedicine, etc. The use of industrial solid waste to prepare foamed ceramic materials can make resource utilization of waste residues and obtain high value-added material products. Therefore, the use of industrial waste residues to prepare foamed ceramic materials has become a hot topic in current research.

[0003] Rare earth blast furnace slag and coal gangue are currently industrial solid waste resources with large production volume and low utilization rate. Rare earth blast furnace slag is a solid waste produced in the process of blast furnace ironmaking, and is a type of solid waste in the metallurgical industry. Rare earth blast furnace slag has been used as a raw material for low value-added products such as cement and engineering backfill, which not only wastes the sensible heat of the slag, but also creates very limited social and economic benefits. The Chinese patent with publication number CN110256047A discloses a method for preparing foamed ceramics using titanium-containing blast furnace slag and shale waste slag. The raw materials are 8-26% by mass of titanium-containing blast furnace slag, 65-80% by mass of shale waste slag, 10-20% by mass of silica powder, 3-3.5% by mass of borax, 5% by mass of ball clay, and 0.3-0.4% by mass of foaming agent. The prepared foamed ceramic has a volume density of 0.216-0.398 g / cm 3 , the compressive strength of the foamed ceramic is 2.231~4.266MPa, and the thermal conductivity is 0.04~0.09W / (m·K). However, this method has the problems of low utilization rate of slag and other solid wastes, low compressive strength of the generated foamed ceramics, and general physical properties.

[0004] Gangue is a solid waste discharged during coal mining and coal washing. The Chinese patent publication with publication number CN118324551A describes a foamed ceramic prepared using fly ash, gangue and magnesium slag, wherein the raw materials used are 20-30 parts of fly ash, 10-20 parts of clay, 20-40 parts of gangue, 5-10 parts of magnesium slag, and 0.3-1.2 parts of foaming agent. After ball milling, spray granulation, and mold filling, the foamed ceramic with an average compressive strength of 10MPa and an average pore size of 1.7mm was obtained by calcining at 1250°C. Although this method solves the problem of low utilization rate of gangue, it also has the defects of long sintering process time, high cost, and low utilization rate of solid waste raw materials.

[0005] The main chemical components of rare earth blast furnace slag are CaO, SiO 2, MgO and Al 2 O 3 The first two have the highest content, and the melting temperature of cold blast furnace slag is relatively high. The main components of coal gangue are SiO 2 、Al 2 O 3 , where Al 2 O 3 The content is relatively high, and the main crystal phase is kaolinite (Al 2 Si 2 O 5 (OH) 4 ), the melting temperature is high, the melting point exceeds 1550℃. Due to the high melting points of rare earth blast furnace slag and coal gangue, the sintering temperature and sintering time of foamed ceramics are greatly affected. It is difficult to directly prepare foamed ceramic materials by combining the two raw materials. A certain amount of low-temperature raw materials and flux need to be added. Therefore, the obtained foamed ceramic materials have the problems of low solid waste utilization rate, general physical properties of the generated foamed ceramics, long sintering process time and high cost.

[0006] Therefore, it is urgent to develop a reasonable method for harmless and resourceful utilization of rare earth blast furnace slag and coal gangue. Summary of the invention

[0007] The present application provides a foamed ceramic prepared by using rare earth blast furnace slag and coal gangue and a preparation method thereof, in order to solve the problems in the above-mentioned background technology.

[0008] In a first aspect, the present application provides a method for preparing foamed ceramics by using rare earth blast furnace slag and coal gangue, comprising:

[0009] The mixture including rare earth blast furnace slag, coal gangue, crushed silica, low melting point solid waste raw materials and talcum powder is ball-milled and crushed to pass through a 200-mesh sieve;

[0010] Add water to the sieved mixture and the foaming agent for wet grinding to obtain a slurry;

[0011] The slurry is dried and then ground to obtain a powder;

[0012] Spreading the powder in a mold and pressing it into shape to obtain a molded blank;

[0013] The formed blank is fired at a high temperature to obtain a foamed ceramic.

[0014] The method of the present application has the following beneficial effects:

[0015] 1) In this application, rare earth blast furnace slag accounts for a high proportion in the mixed material ratio, and is used in combination with solid wastes such as coal gangue and crushed silica, which can greatly improve the utilization rate of rare earth blast furnace slag and multiple solid wastes. Not only can rare earth blast furnace slag and coal gangue be effectively treated at the same time, but also high value-added resource utilization of rare earth blast furnace slag and coal gangue is achieved.

[0016] 2) The method of this application, by adding low melting point solid waste raw materials, not only solves the problem of rare earth blast furnace slag and coal gangue having high melting points and being difficult to burn, but also increases the SiO 2 、Al 2 O 3 And alkali metal oxides (K 2 O、Na 2 O) content, thereby reducing the firing temperature of the foamed ceramic, making the fired pore size uniform and small, improving the physical properties of the foamed ceramic, and ensuring that the preparation process of the foamed ceramic is smooth and smooth.

[0017] 3) In this application, a direct sintering method is used to prepare foamed ceramics, which improves the sintering performance of rare earth blast furnace slag, reduces sintering costs, shortens process time, and makes the production process green and environmentally friendly.

[0018] Optionally, the low melting point solid waste raw materials include shale tailings, lithium feldspar tailings, and waste glass;

[0019] The mixture includes 31-35 parts of rare earth blast furnace slag, 15-20 parts of coal gangue, 20-25 parts of crushed silica, 5-8 parts of leucite tailings, 4-10 parts of lithium feldspar tailings, 8-10 parts of waste glass and 4-5 parts of talc powder by weight.

[0020] Optionally, the temperature-raising firing comprises the following steps:

[0021] The formed blank is placed in a firing device and heated from room temperature to a first temperature in an air atmosphere, and the heating time is controlled to be 30 to 35 minutes;

[0022] The temperature is raised from the first temperature to the second temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the second temperature for 80-110 minutes;

[0023] The temperature is raised from the second temperature to the third temperature, the heating time is controlled to be 90-100 minutes, and the temperature is kept at the third temperature for 120-125 minutes;

[0024] The temperature is raised from the third temperature to the firing temperature, the heating time is controlled to be 40-50 minutes, and the firing temperature is kept at 10-15 minutes;

[0025] The temperature is naturally cooled from the firing temperature to room temperature.

[0026] Optionally, the first temperature is 600-650°C, the second temperature is 900-950°C, the third temperature is 1050-1060°C, and the sintering temperature is 1100-1200°C.

[0027] Optionally, the foaming agent includes one or more of silicon carbide, calcium carbonate, magnesium carbonate, sodium carbonate, calcium sulfate, ferric oxide, graphite, coal, and carbon black;

[0028] The amount of the foaming agent used is 0.1 to 1 part by weight.

[0029] Optionally, the mass percentage of water in the slurry is 40-70%.

[0030] Optionally, during the process of pressing the powder into shape, the pressure used is 20-40 MPa.

[0031] Optionally, the temperature used for the slurry during the drying process is 95-105° C., and the drying time is 3-4 hours.

[0032] Optionally, the particle size of the powder is 300-400 mesh.

[0033] In a second aspect, the present application provides a foamed ceramic prepared by rare earth blast furnace slag and coal gangue, including the foamed ceramic prepared by the method provided in any one of the first aspects above;

[0034] The surface density of foamed ceramic is 30~80kg / m 2 ; The compressive strength of foamed ceramic materials is 4~20MPa, and the bending bearing capacity is ≥1.5.

[0035] The foamed ceramics of the present application can not only make full use of multiple solid waste resources such as rare earth blast furnace slag and coal gangue, but also have the characteristics of low sintering temperature, short sintering time, low cost and good performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0037] Figure 1 A cut-away cross-sectional view of a foamed ceramic sample provided in Example 4 of the present application;

[0038] Figure 2 A cut-away cross-sectional view of a foamed ceramic sample provided in Comparative Example 1 of the present application;

[0039] Figure 3This is a cross-sectional view of the foamed ceramic sample provided in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0041] In a first aspect, the present application provides a method for preparing foamed ceramics by using rare earth blast furnace slag and coal gangue, comprising:

[0042] The mixture including rare earth blast furnace slag, coal gangue, crushed silica, low melting point solid waste raw materials and talcum powder is ball-milled and crushed to pass through a 200-mesh sieve;

[0043] Add water to the sieved mixture and the foaming agent for wet grinding to obtain a slurry;

[0044] The slurry is dried and then ground to obtain a powder;

[0045] Spreading the powder in a mold and pressing it into shape to obtain a molded blank;

[0046] The formed blank is fired at a high temperature to obtain a foamed ceramic.

[0047] In the present application, wet grinding can be used to make the components in the mixture better blended, and due to the presence of water during the wet grinding process, a small amount of each component in the mixture will dissolve in water, and ball milling allows the molecules in different components to blend with each other, which is beneficial to the distribution of each material in the system.

[0048] In this application, the high Al content of coal gangue in the mixture 2 O 3 The content of rare earth blast furnace slag and its high SiO 2 The contents of rare earth blast furnace slag are complementary and can form the supporting skeleton of foamed ceramics. Alkaline earth metal oxides (such as CaO and MgO) in rare earth blast furnace slag can also play a role in regulating the melting point and liquid viscosity of the green body and reducing the firing temperature of the material. During high-temperature sintering, Ca in the mixture combines with Mg, Si and oxygen (O) to form stable diopside (CaMgSi 2 O 6 ) crystal structure. This crystal form makes the prepared foamed ceramics have excellent physical and chemical properties.

[0049] In the present application, rare earth blast furnace slag is a solid waste formed by the gangue in Bayan Obo iron ore, the ash in the fuel and the non-volatile components in the flux during the blast furnace ironmaking process, and is a type of solid waste in the metallurgical industry.

[0050] The mass percentage range of each chemical component in the foamed ceramic of the present application is: SiO 2 50~62%,Al 2 O 3 11~15%, CaO 15~19%, MgO 3~5%, Fe 2 O 3 0.4~0.6%, K 2 O 0.6~1.1%, Na 2 O 1~2.5%.

[0051] In the present application, the particle size of the materials included in the mixture should be less than 5 mm to facilitate subsequent crushing and grinding.

[0052] The mineral components of foamed ceramics include: CaMgSi 2 O 6 (Diopside), SiO 2 (Quartz). The formation of diopside phase and quartz phase improves the sintering performance and mechanical properties of foamed ceramics.

[0053] The method of the present application has the following beneficial effects:

[0054] 1) In this application, rare earth blast furnace slag accounts for a high proportion in the mixed material ratio, and is used in combination with solid wastes such as coal gangue and crushed silica, which can greatly improve the utilization rate of rare earth blast furnace slag and multiple solid wastes. Not only can rare earth blast furnace slag and coal gangue be effectively treated at the same time, but also high value-added resource utilization of rare earth blast furnace slag and coal gangue is achieved.

[0055] 2) The method of this application, by adding low melting point solid waste raw materials, not only solves the problem of rare earth blast furnace slag and coal gangue having high melting points and being difficult to burn, but also increases the SiO 2 、Al 2 O 3 And alkali metal oxides (K 2 O、Na 2 O) content, thereby reducing the firing temperature of the foamed ceramic, making the fired pore size uniform and small, improving the physical properties of the foamed ceramic, and ensuring that the preparation process of the foamed ceramic is smooth and smooth.

[0056] 3) In this application, a direct sintering method is used to prepare foamed ceramics, which improves the sintering performance of rare earth blast furnace slag, reduces sintering costs, shortens process time, and makes the production process green and environmentally friendly.

[0057] Optionally, the low melting point solid waste raw materials include shale tailings, lithium feldspar tailings, and waste glass;

[0058] The mixture includes 31-35 parts of rare earth blast furnace slag, 15-20 parts of coal gangue, 20-25 parts of crushed silica, 5-8 parts of leucite tailings, 4-10 parts of lithium feldspar tailings, 8-10 parts of waste glass and 4-5 parts of talc powder by weight.

[0059] In this application, combined with the characteristics of rare earth blast furnace slag and fly ash, the high CaO and SiO 2 The high SiO content of fly ash 2 and Al 2 O 3 The content can satisfy the requirements of foamed ceramic SiO 2 -Al 2 O 3 -MO (MO stands for CaO and MgO) system. However, due to the high melting point of rare earth blast furnace slag and the complexity of fly ash composition, it is not easy to sinter directly. Therefore, waste glass and talcum powder are added to the two mixtures to increase the alkali metal oxide (K 2 O、Na 2 O) content ratio, a certain amount of alkali metal oxides will reduce the liquid phase formation temperature, reduce the sintering temperature of the material, and increase the amount of liquid phase formed, thereby solving the problem of high melting point and difficult sintering.

[0060] In this application, the proportion of rare earth blast furnace slag in the mixture reaches more than 30%, and the proportion of solid waste materials such as rare earth blast furnace slag, coal gangue, crushed silica, etc. in the mixture for preparing foamed ceramics reaches more than 80%, which greatly improves the utilization rate of rare earth blast furnace slag and multiple solid wastes.

[0061] In this application, the percentages of the components contained in the rare earth blast furnace slag are as follows: 33.67~35% SiO 2 , 14.33~15% Al 2 O 3 , 40.67~41% CaO, 8.33~9% MgO, 0.43~0.45% Fe 2 O 3 , 0.37~0.38% K 2 O, 0.53~0.63% Na 2 O.

[0062] In this application, the percentages of the components contained in the striated rock tailings are as follows: 2 O 4.42~4.44%, MgO 0.28~0.31%, Al 2 O 3 19.8~20.20%, SiO2 65.89~67.13%, P 2 O 5 0.05~0.07%, SO 3 0.12~0.14%, Cl 0.05~0.08%, K 2 O 4.23~4.55%, CaO 1.57~1.71%, TiO 2 0.09~0.11%, MnO 0.02~0.03%, Fe 2 O 3 0.98~1.18%, Rb 2 O 0.01~ 0.02%, SrO 0.01~0.02%, ZrO 2 0.01~0.02%.

[0063] In this application, the percentages of the components contained in the lithium feldspar tailings are as follows: Na 2 O 4.74~5.23%, MgO 0.01~0.03%, Al 2 O 3 16.57~17.77%, SiO 2 70.12~72.41%, P 2 O 5 0.01~0.02%, SO 3 0.05~0.08%, Cl 0.01~0.03%, K 2 O 3.45~3.87%, CaO 0.15~0.22%, MnO 0.03~0.07%, Fe 2 O 3 0.16~0.17%, Rb 2 O 0.08~0.10%, ZrO 2 0.01~0.02%.

[0064] In the present application, the sludge tailings are sludge tailings in Inner Mongolia, and the main mineral components of the sludge tailings are quartz, potassium feldspar and sodium plagioclase.

[0065] The lithium feldspar tailings are Ordos lithium feldspar tailings.

[0066] Optionally, the temperature-raising firing comprises the following steps:

[0067] The formed blank is placed in a firing device and heated from room temperature to a first temperature in an air atmosphere, and the heating time is controlled to be 30 to 35 minutes;

[0068] The temperature is raised from the first temperature to the second temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the second temperature for 80-110 minutes;

[0069] The temperature is raised from the second temperature to the third temperature, the heating time is controlled to be 90-100 minutes, and the temperature is kept at the third temperature for 120-125 minutes;

[0070] The temperature is raised from the third temperature to the firing temperature, the heating time is controlled to be 40-50 minutes, and the firing temperature is kept at 10-15 minutes;

[0071] The temperature is naturally cooled from the firing temperature to room temperature.

[0072] In the present application, the above-mentioned heating process is a uniform heating process to avoid sudden temperature changes that may have adverse effects on the fired ceramics.

[0073] In the method of the present application, by controlling the temperature rise firing process, the sintering time of the foamed ceramic is reduced, the excellent performance of the foamed ceramic is guaranteed, and the foamed ceramic prepared by rare earth blast furnace slag and coal gangue meets the requirements of building wall insulation materials (GB / T23450-2009).

[0074] Optionally, the first temperature is 600-650°C, the second temperature is 900-950°C, the third temperature is 1050-1060°C, and the sintering temperature is 1100-1200°C.

[0075] In the present application, the first temperature is 600-650°C. During this process, the bound water in the material is lost, the waste glass begins to undergo a phase change, and the material begins to soften; the temperature continues to rise to the second temperature. During this process, the foaming agent coal gangue and silicon carbide begin to react with oxygen to produce gas, and at the same time, other high-melting-point components in the material begin to undergo a phase change, or a crystal phase transition; the temperature further rises to the third temperature, the reaction of the foaming agent to produce bubbles is further intensified, most of the materials undergo a phase change and fuse into a new crystal phase, and at the same time, the gas produced by the foaming agent forms many pores inside the system, and the system expands due to the gas production of the foaming agent; when The temperature is further increased to the firing temperature, and the materials in the system are finally fused. The bubbles produced by the foaming agent can not only form pores, but also stir and mix the melted and fused materials. In this process, the materials are more fully fused, and the foaming agent reacts most violently at this stage, producing a large amount of gas. Although the foaming agent produces a large amount of gas, due to the high pressure used during pressing, the materials are tightly compacted. During the firing process, the bubbles produced by the foaming agent will be limited to a certain range to prevent small bubbles from merging into large bubbles, resulting in excessive expansion of the volume of the ceramic, which affects its strength.

[0076] Optionally, the foaming agent includes one or more of silicon carbide, calcium carbonate, magnesium carbonate, sodium carbonate, calcium sulfate, ferric oxide, graphite, coal, and carbon black;

[0077] The amount of the foaming agent used is 0.1 to 1 part by weight.

[0078] In the present application, the above-mentioned foaming agent is an inorganic foaming agent. The foaming principle of this foaming agent is that it decomposes at high temperature to produce gas, thereby forming pores in the ceramic matrix. In the present application, since the gangue contains a small amount of carbon or carbide, and the gangue has a high ignition loss under high temperature conditions, the ignition loss is mainly caused by the evaporation of water in the gangue, the volatilization of organic matter, and the generation of gases such as carbon dioxide and sulfide. The gas generated by the burning of the gangue can generate the pores of the foamed ceramic, so the gangue also plays the role of the foaming agent in the present application. However, due to the complexity of the composition of the gangue and the presence of other volatile substances in the ignition loss, a small amount of small-sized closed pores are generated when it is used alone as a foaming agent. It is difficult to control the pore size and distribution of the foamed ceramic during the sintering process. On this basis, it is necessary to add a small amount of foaming agent that can produce a large amount of gas. The combination of the two can better control the pore size and distribution, make the pore size suitable and evenly distributed, and reduce the cost of the foaming agent.

[0079] Optionally, the mass percentage of water in the slurry is 40-70%.

[0080] In the present application, the slurry is obtained by grinding the mixture and the foaming agent with water. Adding water during the grinding process can avoid the generation of dust during the grinding process, thereby avoiding environmental pollution and material loss. During the wet grinding process, some materials will blend and interlock under the action of water. Moreover, the water content in the slurry is 40~70wt%, which is convenient for later pressing and shaping.

[0081] Optionally, during the process of pressing the powder into shape, the pressure used is 20-40 MPa.

[0082] In the present application, the powder is pressed at a pressure of 20~40MPa, which can make the materials in the mixture squeezed more tightly, which will improve the compatibility of the materials after melting at high temperature during the later firing. Moreover, since the materials are tightly pressed, the pores produced by the foaming agent will be more uniform and dense.

[0083] Optionally, the temperature used for the slurry during the drying process is 95-105° C., and the drying time is 3-4 hours.

[0084] In the present application, when the slurry is dried, the temperature is raised to a preset drying temperature at a rate of 3-5°C / min. The mass ratio of the sieved mixture and the foaming agent to the mass of the grinding balls is 1:3, and the ball milling speed is 80-120 rpm.

[0085] Optionally, the particle size of the powder is 300-400 mesh.

[0086] In the present application, the grinding of the slurry after drying can be carried out by ball milling, rod milling, extrusion crushing and the like. In the present application, ball milling is used because the slurry will clump after drying, and the clumped material can be broken up by grinding. Furthermore, by secondary grinding and crushing of the material, a secondary distribution of each component in the mixture can be achieved, further improving the dispersion of each material. And because some materials will blend and interlock under the action of water during the wet grinding process, the temperature will increase during the drying process, causing the materials to interlock and arrange more closely, and even form a cross-linked body or undergo a crystal phase transition. The cross-linked body formed during the drying process can be redispersed through secondary grinding, which will enable a more stable multi-element cross-linked system to be formed during the later firing process, such as the formation of a stable SiO 2 -Al 2 O 3 -MO (MO stands for CaO and MgO) system. The slurry was sieved through 200 mesh before drying.

[0087] In a second aspect, the present application provides a foamed ceramic prepared by rare earth blast furnace slag and coal gangue, including the foamed ceramic prepared by the method provided in any one of the first aspects above;

[0088] The surface density of foamed ceramic is 30~80kg / m 2 ; The compressive strength of foamed ceramic materials is 4~20MPa, and the bending bearing capacity is ≥1.5.

[0089] The foamed ceramics of the present application can not only make full use of multiple solid waste resources such as rare earth blast furnace slag and coal gangue, but also have the characteristics of low sintering temperature, short sintering time, low cost and good performance. Example

[0090] Example 1

[0091] A foamed ceramic is prepared according to the following method:

[0092] S101. Weigh 31 parts of rare earth blast furnace slag, 17 parts of coal gangue, 25 parts of silica crushed stone, 5 parts of Bayannaoer shale tailings, 9 parts of Ordos lithium feldspar tailings, 8 parts of waste glass, and 5 parts of talc powder by weight, add them into a ball mill, and ball-mill them until they pass a 200-mesh sieve to obtain a crushed material.

[0093] S102. Add 0.1 parts of silicon carbide and water to the crushed material, and perform wet grinding for 20 minutes to obtain a slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120 rpm, the mass proportion of water in the slurry is 40%, and the particle size of the slurry can pass through a 200-mesh sieve.

[0094] S103, drying the slurry at 95°C for 3h, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 120rpm) to obtain a powder with a particle size of 300-400 mesh.

[0095] S104, spreading the powder in a mold, and pressing and molding at a pressure of 20 MPa to obtain a molded blank.

[0096] S105, heating and firing the formed blank to obtain a foamed ceramic;

[0097] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 600°C in an air atmosphere, and the heating time is controlled to be 30 minutes;

[0098] The temperature was raised from 600°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept at this temperature for 90 minutes;

[0099] The temperature was raised from 900°C to 1050°C, the heating time was controlled to be 90 minutes, and the temperature was kept at this temperature for 120 minutes;

[0100] The temperature was raised from 1050°C to 1165°C, the heating time was controlled to be 42 minutes, and the temperature was kept at this temperature for 10 minutes;

[0101] Then cool naturally to room temperature.

[0102] The mineral components of the foamed ceramic material prepared in this embodiment are CaMgSi 2 O 6 (Diopside), SiO 2 (Quartz). The mass percentage of its main chemical components is: SiO 2 57.56%, Al 2 O 3 12.69%, CaO 16.23%, MgO 3.83%, Fe 2 O 3 0.47%, K 2 O 0.86% and Na 2 O 2.02%.

[0103] Example 2

[0104] A foamed ceramic is prepared according to the following method:

[0105] S201. Weigh 33 parts of rare earth blast furnace slag, 20 parts of coal gangue, 20 parts of silica crushed stone, 7 parts of Bayannaoer elephant rock tailings, 8 parts of Ordos lithium feldspar tailings, 8 parts of waste glass, and 4 parts of talcum powder by weight, add them into a ball mill and ball-mill them until they pass a 200-mesh sieve to obtain a crushed material.

[0106] S202. Add 0.1 parts of silicon carbide and water to the crushed material, and wet grind for 20 minutes to obtain a slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120 rpm, the mass proportion of water in the slurry is 50%, and the particle size of the slurry can pass through a 200-mesh sieve.

[0107] S203, drying the slurry at 105°C for 3h, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 120rpm) to obtain a powder with a particle size of 300-400 mesh.

[0108] S204, spreading the powder in a mold, and pressing and molding at a pressure of 30 MPa to obtain a molded blank.

[0109] S205, heating and firing the formed blank to obtain a foamed ceramic;

[0110] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 600°C in an air atmosphere, and the heating time is controlled to be 30 minutes;

[0111] The temperature was raised from 600°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept at this temperature for 90 minutes;

[0112] The temperature was raised from 900°C to 1050°C, the heating time was controlled to be 90 minutes, and the temperature was kept at this temperature for 120 minutes;

[0113] The temperature was raised from 1050°C to 1170°C, the heating time was controlled to be 45 minutes, and the temperature was kept at this temperature for 10 minutes;

[0114] Then cool naturally to room temperature.

[0115] The mineral components of the foamed ceramic material prepared in this embodiment are CaMgSi 2 O 6 (Diopside), SiO 2 (Quartz). The mass percentage of its main chemical components is: SiO 2 55.47%, Al 2 O 3 13.98%, MgO 3.85%, K 2 O 0.91%, CaO 16.52%, Fe 2 O 3 0.48% and Na 2 O 2.03%.

[0116] Example 3

[0117] A foamed ceramic is prepared according to the following method:

[0118] S301. Weigh 35 parts of rare earth blast furnace slag, 17 parts of coal gangue, 25 parts of silica crushed stone, 5 parts of Bayannaoer leucistite tailings, 4 parts of Ordos lithium feldspar tailings, 10 parts of waste glass, and 4 parts of talcum powder by weight, add them into a ball mill and ball-mill them until they pass a 200-mesh sieve to obtain a crushed material.

[0119] S302, adding 0.35 parts of silicon carbide and water to the crushed material, and wet grinding for 40 minutes to obtain slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120rpm, the mass proportion of water in the slurry is 60%, and the particle size of the slurry can pass through a 200-mesh sieve.

[0120] S303, drying the slurry at 95°C for 4 hours, and then ball milling (the mass ratio of material to grinding balls is 1:3, and the ball milling speed is 120 rpm) to obtain a powder with a particle size of 300-400 mesh.

[0121] S304, spreading the powder in a mold, and pressing and molding at a pressure of 40 MPa to obtain a molded blank.

[0122] S305, heating and firing the formed blank to obtain foamed ceramics;

[0123] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 600°C in an air atmosphere, and the heating time is controlled to be 30 minutes;

[0124] The temperature was raised from 600°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept at this temperature for 90 minutes;

[0125] The temperature was raised from 900°C to 1050°C, the heating time was controlled to be 90 minutes, and the temperature was kept at this temperature for 120 minutes;

[0126] Raise the temperature from 1050°C to 1180°C, control the heating time to 50 minutes, and keep it at this temperature for 10 minutes;

[0127] Then cool naturally to room temperature.

[0128] The mineral components of the foamed ceramic material prepared in this embodiment are CaMgSi 2 O 6 (Diopside phase), SiO 2 (Quartz phase). The weight percentages of its main chemical components are: SiO 2 55.47%, Al 2 O 3 12.39%, CaO 17.45%, MgO 4.11%, Fe 2 O 3 0.47%, K 2O 0.71% and Na 2 O 2.03%.

[0129] Example 4

[0130] A foamed ceramic is prepared according to the following method:

[0131] S401. Weigh 31 parts of rare earth blast furnace slag, 17 parts of coal gangue, 25 parts of silica crushed stone, 5 parts of Bayannaoer leucistite tailings, 9 parts of Ordos lithium feldspar tailings, 8 parts of waste glass, and 5 parts of talc powder by weight, add them into a ball mill and ball-mill them until they pass a 200-mesh sieve to obtain a crushed material.

[0132] S402, adding 0.5 parts of silicon carbide and water to the crushed material, and wet grinding for 20 minutes to obtain slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120rpm, the mass proportion of water in the slurry is 70%, and the particle size of the slurry can pass through a 200-mesh sieve.

[0133] S403, drying the slurry at 105°C for 4 hours, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 120 rpm) to obtain a powder with a particle size of 300-400 mesh.

[0134] S404, spreading the powder in a mold, and pressing and molding at a pressure of 35 MPa to obtain a molded blank.

[0135] S405, heating and firing the formed blank to obtain a foamed ceramic;

[0136] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 600°C in an air atmosphere, and the heating time is controlled to be 30 minutes;

[0137] The temperature was raised from 600°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept at this temperature for 90 minutes;

[0138] The temperature was raised from 900°C to 1050°C, the heating time was controlled to be 90 minutes, and the temperature was kept at this temperature for 120 minutes;

[0139] The temperature was raised from 1050°C to 1174°C, the heating time was controlled to be 47 minutes, and the temperature was kept at this temperature for 10 minutes;

[0140] Then cool naturally to room temperature.

[0141] The mineral components of the foamed ceramic material prepared in this embodiment are CaMgSi 2 O 6 (Diopside), SiO 2 (Quartz). The mass percentage of its main chemical components is: SiO2 58.48%, Al 2 O 3 12.71%, CaO 15.58%, MgO 3.77%, Fe 2 O 3 0.47%, K 2 O 0.63% and Na 2 O 2.08%.

[0142] Example 5

[0143] A foamed ceramic is prepared according to the following method:

[0144] S501. Weigh 31 parts of rare earth blast furnace slag, 20 parts of coal gangue, 24 parts of silica crushed stone, 5 parts of Bayannaoer leonine tailings, 6 parts of Ordos lithium feldspar tailings, 10 parts of waste glass, and 4 parts of talc powder by weight, add them into a ball mill and ball-mill them until they pass a 200-mesh sieve to obtain a crushed material.

[0145] S502, adding 1 part of silicon carbide and water to the crushed material, and wet grinding for 35 minutes to obtain slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120rpm, the mass proportion of water in the slurry is 55%, and the particle size of the slurry can pass through a 200-mesh sieve.

[0146] S503, drying the slurry at 105°C for 3.5h, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 120rpm) to obtain a powder with a particle size of 300-400 mesh.

[0147] S504, spreading the powder in a mold, and pressing and molding at a pressure of 35 MPa to obtain a molded blank.

[0148] S505, heating and firing the formed blank to obtain a foamed ceramic;

[0149] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 600°C in an air atmosphere, and the heating time is controlled to be 30 minutes;

[0150] The temperature was raised from 600°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept at this temperature for 90 minutes;

[0151] The temperature was raised from 900°C to 1050°C, the heating time was controlled to be 90 minutes, and the temperature was kept at this temperature for 120 minutes;

[0152] The temperature was raised from 1050°C to 1184°C, the heating time was controlled to be 50 minutes, and the temperature was kept for 10 minutes;

[0153] Then cool naturally to room temperature.

[0154] Example 6

[0155] A foamed ceramic is prepared according to the following method:

[0156] S601. Weigh 35 parts of rare earth blast furnace slag, 15 parts of coal gangue, 20 parts of silica crushed stone, 8 parts of Bayannaoer leucistite tailings, 10 parts of Ordos lithium feldspar tailings, 8 parts of waste glass, and 5 parts of talc powder by weight, add them into a ball mill and ball-mill them until they pass a 200-mesh sieve to obtain a crushed material.

[0157] S602, adding 0.75 parts of silicon carbide and water to the crushed material, and wet grinding for 35 minutes to obtain slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120rpm, the mass proportion of water in the slurry is 55%, and the particle size of the slurry can pass through a 200-mesh sieve.

[0158] S603, drying the slurry at 105°C for 3.5h, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 120rpm) to obtain a powder with a particle size of 300-400 mesh.

[0159] S604, spreading the powder in a mold, and pressing and molding at a pressure of 35 MPa to obtain a molded blank.

[0160] S605, heating and firing the formed blank to obtain foamed ceramics;

[0161] During the heating process, the formed blank was placed in a firing device and heated from room temperature to 650°C in an air atmosphere, and the heating time was controlled to be 35 min;

[0162] The temperature was raised from 650°C to 950°C, the heating time was controlled to be 55 minutes, and the temperature was kept at this temperature for 110 minutes;

[0163] The temperature was raised from 950°C to 1060°C, the heating time was controlled to be 100 min, and the temperature was kept at this temperature for 125 min;

[0164] Raise the temperature from 1060°C to 1100°C, control the heating time to 50 minutes, and keep it at this temperature for 15 minutes;

[0165] Then cool naturally to room temperature.

[0166] Comparative Example 1

[0167] A foamed ceramic is prepared according to the following method:

[0168] The remaining operations are the same as those in Example 4, except that the mixed material includes 40 parts of rare earth blast furnace slag, 21 parts of coal gangue, 16 parts of silicate, 3 parts of Bayannaoer shale tailings, 5 parts of Ordos lithium feldspar tailings, 11 parts of waste glass, and 4 parts of talc. The foaming agent is silicon carbide, and the addition amount is 0.2 parts by weight.

[0169] Comparative Example 2

[0170] A foamed ceramic is prepared according to the following method:

[0171] The remaining operations are the same as those in Example 4, except that the mixed material includes 25 parts of rare earth blast furnace slag, 15 parts of coal gangue, 30 parts of silicate, 6 parts of Bayannaoer shale tailings, 7 parts of Ordos lithium feldspar tailings, 12 parts of waste glass, and 5 parts of talc. The foaming agent is silicon carbide, and the addition amount is 1.3 parts by weight.

[0172] Experimental example

[0173] 1. The foamed ceramics prepared by the methods of Examples 1 to 5 and Comparative Examples 1 to 3 were measured for area density, compressive strength, flexural bearing capacity and water absorption according to the method in GB / T23450-2009 "Thermal insulation strips for building partition walls". The measurement results are shown in Table 1.

[0174] Table 1

[0175]

[0176] From the data analysis of Table 1, it can be seen that the foamed ceramics provided in the embodiments of the present application have excellent mechanical properties, the compressive strength is greater than 4 MPa required by the standard, and the flexural bearing capacity also meets the standard.

[0177] The data of comparative example 1 show that when the addition amount of rare earth blast furnace slag and coal gangue in the mixture is too high, ceramics with loose structure and poor compressive resistance are easily fired. The reason is that coal gangue contains a large amount of carbon and organic matter. During the sintering process, these substances will react with oxygen to form corresponding gaseous oxides or decompose into gaseous materials, thereby generating pores in the ceramics; and rare earth blast furnace slag comes from solid boiling products produced during the blast furnace ironmaking process. During the iron smelting process, lime is added to neutralize the sulfur in the ore, and sulfates are produced in this process. These sulfates will decompose to produce gases such as sulfur dioxide during the sintering process, thereby generating pores inside the ceramics. In addition, variable valence metal oxides in rare earth blast furnace slag, such as iron oxide, will also generate gases during high-temperature sintering. Therefore, when the above-mentioned materials are added in too much amount, a large number of bubbles will be generated during the ceramic sintering process. These bubbles will merge with each other to generate larger bubbles, which will eventually lead to the sintered ceramics with loose structure, large and uneven internal bubbles, and poor mechanical properties.

[0178] The amount of crushed silica used in Comparative Example 2 is 30 parts by weight. Since ethylene silicon dioxide is the main component of crushed silica, the fired foamed ceramic has a high silicon dioxide content, resulting in a dense structure of the foamed ceramic obtained during the firing process. Even if a larger amount of foaming agent is added, the overall foaming effect of the ceramic is not obvious, and the obtained foamed ceramic is mostly small and dense pores, which makes its surface density relatively large.

[0179] 2. The foamed ceramics fired in the above-mentioned Example 4 and Comparative Examples 1 and 2 were cut to display their internal structures. Since the internal structures of the products fired in each example are similar, the foamed ceramic of Example 4 in the example was selected for display. The results are as follows: Figure 1~Figure 3 shown.

[0180] pass Figure 1~Figure 3 It can be seen from the display pictures that the physical properties of the fired foamed ceramics are basically consistent with the measured data in Table 1.

[0181] Example 4 (i.e. Figure 1 The foamed ceramics (shown) have evenly distributed pores inside, relatively uniform pore sizes, and a flat and smooth ceramic surface.

[0182] Comparative Example 1 (i.e. Figure 2 The foamed ceramics (shown in Figure 2) have uneven pore sizes, a large number of large pores, and a relatively loose overall structure.

[0183] Comparative Example 2 (i.e. Figure 3 The foamed ceramics (shown in Figure 1) have basically small bubbles distributed inside and the overall structure is relatively dense.

[0184] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing foamed ceramics by using rare earth blast furnace slag and coal gangue, characterized in that: include: The mixture including rare earth blast furnace slag, coal gangue, crushed silica, low melting point solid waste raw materials and talcum powder is ball-milled and crushed to pass through a 200-mesh sieve; Add water to the sieved mixture and the foaming agent for wet grinding to obtain a slurry; The slurry is dried and then ground to obtain a powder; Spreading the powder in a mold and pressing it into shape to obtain a molded blank; The formed blank is heated and fired to obtain a foamed ceramic; The low melting point solid waste raw materials include shale tailings, lithium feldspar tailings, and waste glass; The mixed material comprises, by weight, 31-35 parts of rare earth blast furnace slag, 15-20 parts of coal gangue, 20-25 parts of crushed silica, 5-8 parts of shale tailings, 4-10 parts of lithium feldspar tailings, 8-10 parts of waste glass, and 4-5 parts of talc; The temperature-raising firing comprises the following steps: The formed blank is placed in a firing device and heated from room temperature to a first temperature in an air atmosphere, and the heating time is controlled to be 30 to 35 minutes; The temperature is raised from the first temperature to the second temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the second temperature for 80-110 minutes; The temperature is raised from the second temperature to the third temperature, the heating time is controlled to be 90-100 minutes, and the temperature is kept at the third temperature for 120-125 minutes; The temperature is raised from the third temperature to the firing temperature, the heating time is controlled to be 40-50 minutes, and the firing temperature is kept at 10-15 minutes; The temperature is naturally cooled from the firing temperature to room temperature; The first temperature is 600-650°C, the second temperature is 900-950°C, the third temperature is 1050-1060°C, and the firing temperature is 1100-1200°C; the foaming agent includes silicon carbide, and the amount of the foaming agent used is 0.1-1 parts by weight; The temperature used in the slurry drying process is 95~105℃, and the drying time is 3~4h; During the process of pressing the powder into shape, the pressure used is 20~40MPa.

2. The method for preparing foamed ceramics by using rare earth blast furnace slag and coal gangue according to claim 1, characterized in that: The foaming agent also includes one or more of calcium carbonate, magnesium carbonate, sodium carbonate, calcium sulfate, ferric oxide, graphite, coal, and carbon black.

3. The method for preparing foamed ceramics by using rare earth blast furnace slag and coal gangue according to claim 1, characterized in that: The mass percentage of water in the slurry is 40-70%.

4. The method for preparing foamed ceramics by using rare earth blast furnace slag and coal gangue according to any one of claims 1 to 3, characterized in that The particle size of the powder is 300-400 meshes.

5. A foamed ceramic prepared by using rare earth blast furnace slag and coal gangue, characterized in that: It comprises being prepared by the method described in any one of claims 1 to 4 above; The surface density of the foamed ceramic is 30-80 kg / m 2 ; The compressive strength of the foamed ceramic material is 4~20MPa.

Citation Information

Patent Citations

  • Method for preparing foaming ceramic by using titaniferous blast furnace slag and shale waste residue

    CN110256047A

  • Foaming ceramic prepared from fly ash, coal gangue and magnesium slag as well as preparation method and application of foaming ceramic

    CN118324551A

  • Preparation method of foamed ceramic thermal insulation material as well as product thereof

    CN103553701A

  • Manufacturing method of foamed ceramic plate

    CN114671701A

Cited By

  • Preparation method of road slope reinforcement and ecological regulation composite material based on biological mixed mediation mineralization

    CN121270162A